Constructive side-channel analysis and secure design : 7th International Workshop, COSADE 2016, Graz, Austria, April 14-15, 2016, Revised selected papers /: 7th International Workshop, COSADE 2016, Graz, Austria, April 14-15, 2016, Revised selected papers. (2016) - Unknown
No abstract available